The development of inquiry-learning activities with multimedia for enhancing learning achievement on foreign languahes in thai languge for matthayomsuksa 4 students - Khunkaew, Jirapinya; Sujaree, Tipaporn; Pharanat, Wanida (Journal for Developing the Social and Community, 2025)
Background and Aims: The Thai language, as the national language, embodies the identity, culture, and accumulated wisdom of the Thai people. It serves as a crucial medium for communication, enabling the expression of thoughts, emotions, and diverse bodies of knowledge, while fostering mutual understanding and harmonious relationships within society. Furthermore, it provides a foundational basis for the learning of other disciplines and constitutes a significant factor in improving the quality of life and professional advancement of the populace. Methodology: This research aimed to study the effectiveness of inquiry-based learning activities integrated with multimedia in enhancing the learning achievement of Grade 10 students. The sample consisted of Grade 10 students from Sarakhampittayakhom School, Mueang District, Maha Sarakham Province, under the Office of Secondary Educational Service Area, Maha Sarakham, in the academic year 2024, selected through the cluster random sampling technique. The research instruments comprised: (1) inquiry-based learning activities integrated with multimedia, (2) a learning achievement test on “Loanwords in the Thai Language,” and (3) a student satisfaction questionnaire.The results revealed that: (1) the inquiry-based learning activities integrated with multimedia had an efficiency of 90.92 / 83.33, which exceeded the specified criterion; (2) the students’ post-learning achievement scores were significantly higher than their pre-learning scores at the .05 level of statistical significance; and (3) the students’ overall satisfaction with the activities was at the highest level (X̅ = 4.64, S.D. = 0.29). Results: The findings suggest that inquiry-based learning integrated with multimedia is effective in improving student learning achievement and can be appropriately applied to learners at higher educational levels. Conclusion: The implementation of inquiry-based learning activities in conjunction with multimedia has been found to effectively enhance the academic achievement of Grade 10 students and can be suitably applied to the development of learners at higher educational levels.